A feminist critique of the public security response to violence against women - Barroso, Milena Fernandes; Ribeiro Lima, Raissa (Argumentum, 2020)
From the perspective of critical feminist criminology, this article discusses how public security institutions are addressing violence against women. In the first section, we present a brief debate on current issues of public security, highlighting the contradictions and challenges surrounding the criminalization of violence against women. Next, we analyze research data collected in 2019 from the public security institutions of the city of Parintins, Amazonas, to understand the dynamics of assistance for women at risk of violence. The study points out the need for and importance of a feminist critique of punitive measures in the fight against violence, as well as reaffirming the neglect of these institutions in protecting women, even though they are the primary gateway to other related care services.Keywords: Violence against women. Public security. Critical feminist criminology. Parintins. Amazonas.